Exclusive breastfeeding and risk of atopic dermatitis in high risk infant - Martaviani Budiastuti, Setya Wandita, Sumadiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: WHO recommends exclusive breast-feeding for 6 months becaase it is highly beneficial. It hasbeen proven by a number of studies to be advantageous in preventing various infectious diseases. However,its role in preventing allergic diseases especially atopic dermatitis in infant remains uncertain until recently.Objective: To find out whether high risk infant who did not receive exclusive breast-feeding would have agreater risk to suffer from atopic dermatitis.Method: We conducted a case-control study. Data were obtained from Pediatric Outpatient Clinics andDermatology and Venerology Outpatient Clinics, Dr. Sardjito Hospital Yogyakarta. Case group was highrisk infants with atopic dermatitis, while control group was high risk infants but not having the disease.Statistical analysis used Chi-square and degree of significance was stated as Confidence Interval (CI) of95% for each Odds Ratio (OR). Multivariate analysis was performed by using logistic regression method.Results: The study included 88 subjects with 44 subjects for case and control groupas well Logisticregression showed that not receiving exclusive breast-feeding was statistically significant risk factor toatopic dermatitis in high risk infant OR 3.72 (95% CI: 1.40-9.90); p 0.01.Conclusion: High risk infant not receiving exclusive breast-feeding will have greater risk to develop atopicdermatitis.Keywords: exclusive breast-feeding, atopic dermatitis; high risk infants.